2022
DOI: 10.3390/cancers14020380
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body MRI Surveillance—Baseline Findings in the Swedish Multicentre Hereditary TP53-Related Cancer Syndrome Study (SWEP53)

Abstract: A surveillance strategy of the heritable TP53-related cancer syndrome (hTP53rc), commonly referred to as the Li–Fraumeni syndrome (LFS), is studied in a prospective observational nationwide multi-centre study in Sweden (SWEP53). The aim of this sub-study is to evaluate whole-body MRI (WB-MRI) regarding the rate of malignant, indeterminate, and benign imaging findings and the associated further workup generated by the baseline examination. Individuals with hTP53rc were enrolled in a surveillance program includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Baseline demographic characteristics are shown in Table 1, with further details in Table S1. After undergoing a baseline WB‐MRI, three asymptomatic participants were diagnosed with cancer 12 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Baseline demographic characteristics are shown in Table 1, with further details in Table S1. After undergoing a baseline WB‐MRI, three asymptomatic participants were diagnosed with cancer 12 …”
Section: Resultsmentioning
confidence: 99%
“…In the Swedish TP53 Study (SWEP53), adult carriers are offered routine surveillance with WB‐MRI including MRI of the breasts and brain. Our first publication indicated 30 imaging findings in 19 of 61 participants (31%) of which 21 lesions in 16 individuals (84%) were incidental and nonmalignant 12 . Until now, studies evaluating the psychosocial impact of surveillance with WB‐MRI have been reported from Australia, 13 Great Britain, 14 Germany, 15 and the United States, 16,17 including 17–49 study participants.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, as a rule, the types of tumors are evaluated from time to time and the therapies used for classic cancer patients are adopted. Several studies have shown that active surveillance of LFS patients is significantly associated with improved survival by tracking presymptomatic malignancies compared to LFS patients who were diagnosed with cancer because the symptoms arose [ 15 , 94 , 95 , 96 , 97 ]. Overall, these studies propose clinical surveillance protocols using physical examination and frequent biochemical and imaging studies for instance consisting of whole-body magnetic resonance imaging (MRI), specific MRI of brain breast, mammography, abdominal and pelvic ultrasound, and colonoscopy.…”
Section: Tumor Prevention and Treatmentsmentioning
confidence: 99%
“…Several global studies, mostly conducted without gadolinium-based contrast agents (GBCAs), have validated the effectiveness of WBMRI, showing an overall estimated detection rate of 7% for new and localised primary cancers during the initial screen [ 8 , 12 , 13 ]. Given the potential long-term retention of GBCAs in various organs, it is recommended that caution is exercised when administering multiple GBCAs to germline TP53 variant carriers.…”
Section: Introductionmentioning
confidence: 99%